Pengaruh Social Media Marketing Activity Terhadap Keputusan Pembelian Tas Bostanten di TikTok Shop Dengan Brand Trust Sebagai Variabel Mediasi (Studi Pada Gen Z Kabupaten Nganjuk) - Zurina Endra Sari; Yustina Chrismardani (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to determine the effect of social media marketing activity on purchasing decisions of Bostanten bags on TikTok Shop, with brand trust as a mediating variable, focusing on Generation Z in Nganjuk Regency. This research uses a quantitative approach with both primary and secondary data. Data were collected through a questionnaire distributed to 97 respondents selected using purposive sampling. The data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4.1 software. The results show that social media marketing activity has a significant effect on brand trust and purchasing decisions. In addition, brand trust also has a significant influence on purchasing decisions. The findings further indicate that brand trust partially mediates the effect of social media marketing activity on purchasing decisions